ANALISIS SEKTOR UNGGULAN DAN STRATEGI PENGEMBANGANNYA DALAM MENINGKATKAN PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN TIMOR TENGAH UTARA (TTU) - Khristina Kiha, Emilia; Korbaffo, Yesus Armiro (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The purpose of this study is to determine the mapping of leading sectors, what are the basic sub-sectors in the leading sector and how will the change in the position of the base sector in the leading sector in the future and how the strategy of developing leading sectors in North Central Timor Regency. data analysis using Location Questient (LQ) and Dynamic Location Questient (DLQ). Based on various analyzes that have been carried out on 17 economic sectors, there are 5 LQ sectors> 1 namely Agriculture, Forestry, and Fisheries, Mining and Quarrying, Transportation and Warehousing, Real Estate and Government Administration, Defense and Mandatory Social Security sectors. Whereas the DLQ analysis calculation shows that there are 15 economic sectors that are expected to be based in the future or DLQ> 1. Where are the five sectors, namely Agriculture, Forestry and Fisheries, Mining and Quarrying, Transportation and Warehousing, Financial Services and Insurance and Government Administration as well as Defense and Compulsory Social Security belonging to the base sector are still classified as the base sector in the future. While 10 sectors, namely the manufacturing industry sector, the electricity and gas procurement sector, the construction sector, wholesale and retail trade; the Car and Motorcycle Repair sector, the Provision of Accommodation and Food and Beverage, the Information and Communication sector, the Financial Services and Insurance sector, the Corporate Services sector, the Education Services sector, the Health Services sector and the Social Activities sector which will only become a base sector in the future.